2012
DOI: 10.1186/1751-0759-6-15
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial problems of Pakistani parents of Thalassemic children: a cross sectional study done in Bahawalpur, Pakistan

Abstract: BackgroundThalassemia is a blood disorder passed down through families (inherited) in which the body makes an abnormal form of hemoglobin. This disorder results in excessive destruction of red blood cells, and there is no effective treatment. Patients require lifelong blood transfusion, usually started within 6 to 12 months of birth of patient, which on other hand has its own complications. It is a chronic disease that manifests so early in life that it leads to psychological and social problems for parents . … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 4 publications
7
14
1
Order By: Relevance
“… 13 Mean age of our patients was 17 years, it is comparable to studies conducted in Taiwan 14 and Egypt. 15 Mean age of our caregivers was 41.25 years, it is similar to researches conducted in Rawalpindi 16 , Bahawalpur 17 and Greece. 18 No significant association was seen between stress in relation gender of patients and caregivers in the study conducted in India 19 and Greek transfusion center 6 , which is also similar to our results.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“… 13 Mean age of our patients was 17 years, it is comparable to studies conducted in Taiwan 14 and Egypt. 15 Mean age of our caregivers was 41.25 years, it is similar to researches conducted in Rawalpindi 16 , Bahawalpur 17 and Greece. 18 No significant association was seen between stress in relation gender of patients and caregivers in the study conducted in India 19 and Greek transfusion center 6 , which is also similar to our results.…”
Section: Discussionsupporting
confidence: 80%
“…In a study conducted in Bahawalpur, Pakistan, 45% of caregivers were psychologically distressed. 17 The status of education among caregivers had no influence on the levels of stress and our study also showed no such difference with level of education statistically. 15 …”
Section: Discussioncontrasting
confidence: 39%
“…In many rural areas of Pakistan, due to traditional cultural practices, blind religious believes, ignorance and pressure from family and society, parents of thalassemic child face many problems in the treatment of their sick child (Aziz et al 2012 ) along with their social adjustment (Shaligram et al 2007 ). Beside medical and professional support, these people required awareness, acceptance, recognition and removal of social pressure to manage the disease and knob these decisive circumstances (Roy and Chatterjee 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thalassemia begins from infancy and has several mental effects on parents. Lack of training causes numerous social problems for parents (17). Mazzone and et al stated that family having a child with thalassemia have numerous problems (18).…”
Section: Discussionmentioning
confidence: 99%